The Effects of Hyperacute Serum on the Elements of the Human Subchondral Bone Marrow Niche - Melinda Simon; Bálint Major; Gabriella Vácz; Olga Kuten; István Hornyák; Adél Hinsenkamp; Dorottya Kardos; Marcell Bagó; Domonkos Cseh; Adrienn Sárközi; Denes Horvathy; Stefan Nehrer; et al. (Stem Cells International)
Mesenchymal stem cells (MSCs) are widely used in laboratory experiments as well as in human cell therapy. Their culture requires animal sera like fetal calf serum (FCS) as essential supplementation; however, animal sera pose a risk for clinical applications. Human blood derivatives, for example, platelet-rich plasma (PRP) releasates, are potential replacements of FCS; however, it is unclear which serum variant has the best effect on the given cell or tissue type. Additionally, blood derivatives are commonly used in musculoskeletal diseases like osteoarthritis (OA) or osteonecrosis as “proliferative agents” for the topical MSC pool. Hyperacute serum (HAS), a new serum derivative, has been designed to approximate the natural coagulation cascade with a single-step, additive-free preparation method. We investigated the effects of HAS on monolayer MSC cultures and in their natural niche, in 3D subchondral bone and marrow explants. Viability measurements, RT-qPCR evaluation for gene expression and flow cytometry for cell surface marker analysis were performed to compare the effects of FCS-, PRP-, or HAS-supplemented culture media. Monolayer MSCs showed significantly higher metabolic activity following 5 days’ incubation in HAS, and osteoblast-specific mRNA expression was markedly increased, while cells also retained their MSC-specific cell surface markers. A similar effect was observed on bone and marrow explants, which was further confirmed with confocal microscopy analysis. Moreover, markedly higher bone marrow preservation was observed with histology in case of HAS supplementation compared to FCS. These findings indicate possible application of HAS in regenerative solutions of skeletal diseases like OA or osteonecrosis.